The impact of parental employment trajectories on children’s early adult education and employment trajectories in the finnish birth cohort 1987 - Haapakorva Pasi; Ristikari Tiina; Gissler Mika (Society for Longitudinal and Life Course Studies, 2025)
The Finnish Birth Cohort 1987 grew up during the recession that hit Finland in the early 1990s, which had an impact on their parents’ activity in the labour market. In this paper we use Finnish register data to build employment and education sequences for all young people born in Finland in 1987 for the period 2005–2012 and employment sequences for all their parents for the entire length of their children’s lives from 1987 until 2012. The sequences were analysed and clustered, and four multinomial logistic regression models were used to find how parents’ trajectories connect to their children’s early adulthood trajectories. Most parents had been on a stable employment trajectory, but we found mothers and fathers who were absent from the labour market during the recession of the 1990s and after it – and some parents never entirely returned to work during this 1987–2012 follow-up. Likewise, most children were either on an employment or education trajectory, but we found groups of children who were on very early child care trajectories, unemployment trajectories, or on a trajectory with no records in the Finnish registers, which in the Finnish context implies that those young people are not employed, not in education and not receiving any of the various benefits. Disadvantageous trajectories were mostly very lasting. We found strong connections between parents’ disadvantages in the labour market and children’s disadvantageous early adulthood trajectories, even when adjusting for strong background variables. The strongest connections arise from parents’ long absences from the labour market.